Comparative study on the efficiency of employees in unionized and non-unionized private business organizations - Arungayan, Alfredo III, A.; Espinosa, Mark.; Jacela, Juanito; Reyes, Ariel; Sacayanan, Joan. (1996.)
This study aims to compare the effect of efficiency of unionization and non-unionization to efficiency of employees in private business organizations. The private business organizations include PECO, ILIASCO, Libcap, and UCPB. This study was done through a survey conducted among 60 respondents, 15 each from the companies above. Findings show that only 26.67% of the unionized respondents think they belong to a very good efficiency level and 50% of the non-unionized respondentss think they are at a very good efficiency level. On the whole, the study indicated that there is no difference on the efficiency of unionized and non-unionized employees.
Research Paper (Mgt 200-Management Research). -- [Iloilo City] : University of the Philippines in theVisayas -College of Management, [1996].